Family‐level variation in early life‐cycle traits of kelp. Issue 2 (10th January 2019) - Mabin, Christopher J. T.; Johnson, Craig R.; Wright, Jeffrey T.
Abstract : Temperate kelp forests (Laminarians) are threatened by temperature stress due to ocean warming and photoinhibition due to increased light associated with canopy loss. However, the potential for evolutionary adaptation in kelp to rapid climate change is not well known. This study examined family‐level variation in physiological and photosynthetic traits in the early life‐cycle stages of the ecologically important Australasian kelp Ecklonia radiata and the response of E. radiata families to different temperature and light environments using a family × environment design. There was strong family‐level variation in traits relating to morphology (surface area measures, branch length, branch count) and photosynthetic performance ( F v / F m ) in both haploid (gametophyte) and diploid (sporophyte) stages of the life‐cycle. Additionally, the presence of family × environment interactions showed that offspring from different families respond differently to temperature and light in the branch length of male gametophytes and oogonia surface area of female gametophytes. Negative responses to high temperatures were stronger for females vs. males. Our findings suggest E. radiata may be able to respond adaptively to climate change but studies partitioning the narrow vs. broad sense components of heritable variation are needed to establish the evolutionary potential of E. radiata to adapt under climate change.